THE DETERMINANTS, SIGNIFICANCE AND IMPACT OF FOREIGN INSTITUTIONAL INVESTMENTS: AN INDIAN STANDPOINT - Shah, Karan (2010)
Ever since policymakers implemented the decision to liberalize India’s economy, allowing foreign investors to purchase assets in the Indian capital markets, India has been attracting investors globally to invest in its growth story. Since this liberalization in 1991, India has gone on to become to become an international hotspot for foreign investment , with the Indian economy going on to become the most rapidly growing economy, second only to China. Foreign Institutional Investors have played their part in boosting this economic growth by helping to finance it, and influencing the modernization and discipline of the India’s capital markets.